SUMO Is a Critical Regulator of Salt Stress Responses in Rice . Issue 4 (11th February 2016) - Srivastava, Anjil Kumar; Zhang, Cunzin; Yates, Gary; Bailey, Mark; Brown, Adrian; Sadanandom, Ari
Abstract : The OsOTS1 SUMO protease acts in the nucleus to promote root growth and confer salt tolerance. Abstract: SUMO (Small Ubiquitin-like Modifier) conjugation onto target proteins has emerged as a very influential class of protein modification systems. SUMO1/2 double mutant plants are nonviable, underlining the importance of SUMO conjugation to plant survival. Once covalently bound, SUMO can alter a conjugated protein's stability and/or function. SUMO conjugation is a highly dynamic process that can be rapidly reversed by the action of SUMO proteases. The balance between the conjugated/deconjugated forms is a major determinant in the modulation of SUMO-target function. Despite the important mechanistic role of SUMO proteases in model plants, until now the identity or the function of these regulatory enzymes has not been defined in any crop plant. In this report, we reveal the ubiquitin-like protease class of SUMO protease gene family in rice ( Oryza sativa ) and demonstrate a critical role for OsOTS1 SUMO protease in salt stress. OsOTS -RNAi rice plants accumulate high levels of SUMO-conjugated proteins during salt stress and are highly salt sensitive; however, in non-salt conditions, they are developmentally indistinguishable from wild-type plants. Transgenic rice plants overexpressing OsOTS1 have increased salt tolerance and a concomitant reduction in the levels of SUMOylated proteins. We demonstrate that OsOTS1 confers salt tolerance in rice by increasing root biomass. High salinity triggers OsOTS1 degradation, indicating that increased SUMO conjugation in rice plants during salt stress is in part achieved by down-regulation of OTS1/2 activity. OsOTS1 is nuclear localized indicating a direct requirement of OsOTS1 -dependent deSUMOylation activity in rice nuclei for salt tolerance.